Navigating the path to pharmacy excellence: A warm welcome for first-year students / Dr. Mohd Shahezwan Abd Wahab ... [et al.] - Abd Wahab, Mohd Shahezwan; Osman, Nurul Izzati; Kwong Siew, John Shia; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
On October 4, 2023, the Office of Academic Affairs, Faculty of Pharmacy, UiTM Puncak Alam, conducted an academic briefing for the 211 first-year students enrolled in the PH240 Bachelor of Pharmacy (Hons.) programme as part of the university's Education 5.0-week initiative. The session aimed to provide new students with essential information about the faculty and the comprehensive Bachelor of Pharmacy curriculum. The session, carefully crafted to meet the freshmen's needs, will serve as a valuable resource to help them navigate through their academic journey. The students gained insights into the faculty's distinguished reputation, its dedicated faculty members, and the exceptional opportunities it offers to shape their pharmacy career.